Facile synthesis of magnetite iron oxide nanoparticles via precipitation method at different reaction temperatures - Tai, M.F.; Lai, Chin Wei; Hamid, Sharifah Bee Abd; Suppiah, Durga Devi; Lau, K.S.; Yehya, W.A.; Julkapli, N.M.; Lee, W.H.; Lim, Y.S. (Taylor & Francis, 2014)
The nano-scale magnetite iron oxide particles have been synthesised by a facile precipitation method. Magnetite iron oxide nanoparticles were synthesised in a bath with electrolytes composed of 0·10 M of iron (II) chloride with 0·45 M of sodium hydroxide at different reaction temperatures under oxidising environment. In the present study, the influence of reaction temperatures (30, 45 and 80°C) on the morphology, particle size and crystallinity of the iron oxide particles were investigated in detail. Based on the Malvern Zetasizer analysis, the iron oxide particles with variable size from ∼250 to ∼70 nm could be achieved when increasing the reaction temperature up to 80°C. The magnetite phase of iron oxide particles was determined by using X-ray diffraction analysis. In addition, field emission scanning electron microscopy micrographs were further affirmed that our synthesised iron oxide particles were in nano-scale with a spherical shape. It was found that the high reaction temperature is helpful in controlling the formation of uniform magnetite iron oxide nanoparticles.